The influence of Islamic spirituality in the training of co-operatives’ managers in Malaysia - Sarif, Suhaimi Mhd; Ismail, Yusof (2011)
Islamic spirituality is under the Tawhidic paradigm (Unity of God), which links worldly deed with the consequences in the Hereafter (al Akhirah) (the Hereafter). In the training of cooperatives’ managers, one must possess knowledge (al ‘ilm) and understanding (al fahm) of the Tawhidic paradigm, and related values and principles before applying them to specific organizational contexts. The training module should integrate Tawhidic paradigm with Mintzberg’s managerial roles that explain the actual work that managers do into ten (10) specific managerial roles and classified them into three areas: (a) interpersonal, (b)informational, and (c)decisional. While managers of conventional companies are governed by the Companies Act 1965 under the Companies Commission of Malaysia, co-operative organizations are administered by the Co-operative Act 1963 under the supervision of the Co-operative Commission of Malaysia. This paper investigates the perceptions of co-operatives’ senior managers toward managerial roles and their training within the co-operatives’ framework and Islamic spirituality. The results showed that senior managers of co-operatives performed Mintzberg’s managerial roles consciously with Islamic spirituality and attended managerial training like their companies counterparts despite operating under different legal frameworks.However, the results were not conclusive considering constraints on sample size of the study (n=52). The study proposed that future research use case study method to understand the details of managerial work at cooperatives.